Assessing the Impact of Subsidy loans from Rotary Club on Paddy farmers’ productivity in Kilinochchi, Sri Lanka - Ratheeban, P.; Sooriyakumar, K.; Sarujan, S.; Sivashankar, S. (Wayamba University of Sri Lanka, 2025)
Agricultural credit is aimed to improve farm productivity of small-scale farmers. However, the effectiveness of agricultural credit remains questionable due lack of credit access and awareness on formal credit channels, especially among the small-scale farmers. This study investigates the productivity impact of a loan-scheme with the subsidized interest rate of 4%, provided from Rotary Club to the paddy farmers in Kilinochchi district, Sri Lanka, using Propensity Score Matching (PSM) to control for selection bias (i.e., small-scale farmers who have good contact with the agrarian centres and registered under other incentive schemes are more likely to be chosen as beneficiaries) and confounding factors such as farmer's experience, technology use, access to extension services etc. Data were collected through a comprehensive survey conducted between August and September, encompassing 57 subsidy loan recipients and 58 subsidy loan non-recipients, selected via random sampling. The survey gathered detailed information on demographic characteristics, financial information, inputs for paddy cultivation, and socio-economic variables through personal interviews using a structured questionnaire. Analysis of the study revealed significant impact of subsidy loans on paddy productivity. The average treatment effect was not significant effect in paddy productivity whereas The Average Treatment Effect on the Treated (ATET) indicates a remarkable enhancement in productivity, with treated farmers obtained 153 kg/acre more yield. The finding emphasizes the importance of providing subsidy loans to improve farm productivity.
Keywords: Treatment effect; Paddy farmers; Paddy productivity; Propensity score matching; Subsidy loan